Atypical Pyoderma Gangrenosum - Lane, Tanda N.; Cargill, John; Lane, Joshua E. (Archives of Clinical and Medical Case Reports, 2026)
Pyoderma gangrenosum is an uncommon neutrophilic skin disorder that varies in presentation. The presence of ulceration is common and diagnosis is often based on exclusion of other entities. A wide variety of treatment options exist; however, cure is often still difficult. The presence of underlying systemic disease must be considered. Herein, we report an atypical case of pyoderma gangrenosum and review current therapeutic modalities.